Impression management – an international perspective - Maria-Silvia Sandulescu (Audit Financiar, 2017)

(untitled)
The purpose of this paper is to perform a review of the international literature regarding impression management by presenting the inherent strategies and their potential impact on the users of accounting information. The concept involves creating a favorable image regarding the financial performance of the company and using it in order to manipulate the decisions of the users of accounting information. The persuasion within corporate narratives overrules the fundamental characteristic of information, namely faithful representation. Consequently, knowing the impression management strategies facilitates their identification and lowers their efficiency and negative effects. As a result, the present study analyzes the main research papers published from 2000 to 2015 in an international background that investigates the impression management concept. Finally, future research opportunities are identified.